1999
DOI: 10.1002/(sici)1098-2396(19991215)34:4<256::aid-syn2>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Opioid peptide receptor studies. 10. Nor-BNI differentially inhibits kappa receptor agonist-induced G-protein activation in the guinea pig caudate: Further evidence of kappa receptor heterogeneity

Abstract: There is strong evidence supporting the existence of multiple kappa receptors. Previous studies proposed that U69,593 and (+)-tifluadom act on different kappa receptor subtypes, kappa(1) (kappa(1)) and kappa(2) (kappa(2)), respectively. In this study, we investigated the effects of the kappa selective antagonist nor-binaltorphimine (Nor-BNI) on U69,593- and (+)-tifluadom-induced receptor-mediated stimulation of [(35)S]-GTP-gamma-S binding in the guinea pig caudate. The IC(50) value of Nor-BNI in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…To date, only one KOPr receptor type (KOPr-1: KOPr) has been cloned. Although pharmacological data indicate the existence of multiple KOPr receptor subtypes (KOPr-1, KOPr-2, KOPr-3) (Heyliger et al, 1999;Horan et al, 1993), a clear demonstration of KOPr heterogeneity has proved elusive. A recent study (Olianas et al, 2006) has shown that the prototypic KOPr-3 agonist, naloxonebenzoylhydrazone, is a partial agonist at the cloned μ-(MOPr), δ-(DOPr), and KOPr as well as an antagonist at opioid-like nociceptin receptors.…”
Section: Physiology and Pharmacology Of Dyn/ Kopr Systemsmentioning
confidence: 99%
“…To date, only one KOPr receptor type (KOPr-1: KOPr) has been cloned. Although pharmacological data indicate the existence of multiple KOPr receptor subtypes (KOPr-1, KOPr-2, KOPr-3) (Heyliger et al, 1999;Horan et al, 1993), a clear demonstration of KOPr heterogeneity has proved elusive. A recent study (Olianas et al, 2006) has shown that the prototypic KOPr-3 agonist, naloxonebenzoylhydrazone, is a partial agonist at the cloned μ-(MOPr), δ-(DOPr), and KOPr as well as an antagonist at opioid-like nociceptin receptors.…”
Section: Physiology and Pharmacology Of Dyn/ Kopr Systemsmentioning
confidence: 99%